Existing views about the electrical properties of whiskers, their analysis - Артемьев, Сергей Робленович (Eastern-European Journal of Enterprise Technologies, 2014)
The results of studies of electrical and structure-sensitive properties of various groups of whiskers are considered, the effect of the electrical properties on the whisker structure is shown, the results of studies of occurrence of the charged layers on the whisker surface is analyzed. Analysis of literature data suggests that there no so many research papers and publications, specifically devoted to the study of the electrical properties of metallic whiskers. There is also an obvious deficiency in contemporary publications, although some authors considered promising application areas of "whiskers" taking into account the impact of their characteristics on the development of specific research areas. The issues of implementing new processing technologies of whiskers, the possibilities of creating biocompatible materials on their basis are analyzed and discussed in some publications. In thesis works, the properties of whiskers as nanomaterials are investigated, physical properties of single crystals are considered in depth and special attention is paid to the optical properties. Almost all researchers noted and note that the electrical properties of whiskers are predetermined by an ideal crystal lattice structure, the presence of defects on the surface and possible presence of trace impurities. Eventually, accounting and justification of a particular group of whiskers properties will allow not only obtaining high-quality products, but also fulfilling human and environmental protection requirements.